2020
DOI: 10.1038/s41467-020-16402-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular molds for regularizing Kondo states at atom/metal interfaces

Abstract: Adsorption of magnetic transition metal atoms on a metal surface leads to the formation of Kondo states at the atom/metal interfaces. However, the significant influence of surrounding environment presents challenges for potential applications. In this work, we realize a novel strategy to regularize the Kondo states by moving a CoPc molecular mold on an Au(111) surface to capture the dispersed Co adatoms. The symmetric and ordered structures of the atom-mold complexes, as well as the strong d π-π bonding betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…71,72 The HEOM approach has been widely used to study a variety of static and dynamic properties of strongly correlated quantum impurity systems in and out of equilibrium. 62,63,[73][74][75][76][77][78][79] In the framework of the HEOM, the influence of the noninteracting leads on the impurity is fully captured by the hybridization functions, Γ α (ω) ≡ π k |t αk | 2 δ(ω − ǫ αk ). For numerical convenience, a Lorentzian form of Γ α (ω) = ∆αW 2 α (ω−Ωα) 2 +W 2 α is adopted, where ∆ α is the effec-tive coupling strength between the impurity and the αth lead, and Ω α and W α are the band center and width of the αth lead, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…71,72 The HEOM approach has been widely used to study a variety of static and dynamic properties of strongly correlated quantum impurity systems in and out of equilibrium. 62,63,[73][74][75][76][77][78][79] In the framework of the HEOM, the influence of the noninteracting leads on the impurity is fully captured by the hybridization functions, Γ α (ω) ≡ π k |t αk | 2 δ(ω − ǫ αk ). For numerical convenience, a Lorentzian form of Γ α (ω) = ∆αW 2 α (ω−Ωα) 2 +W 2 α is adopted, where ∆ α is the effec-tive coupling strength between the impurity and the αth lead, and Ω α and W α are the band center and width of the αth lead, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The rich functionalities of porphyrin complexes orginate from the center macrocycle, which can stablize a variety of elements inside and thus gives rise to distinct structural, electronic, magnetic, optoelectronic, and transport properties [4][5][6][7][8][9][10][11][12][13] . Magnetic metalloporphyrins have been extensively studied by various techniques, exhiting kondo and spin excitation effects, Yu-Shiba bound states, and spin-state switching [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . Recently, hybridized graphene and metalloporphyrin nanostructures have been achieved, hosting combined intriguing electronic and magnetic properties [28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…34 Recently, we have successfully used cobalt phthalocyanine (CoPc) molecules as molds to regularize the local spin states of Co atoms dispersed on an Au(111) surface. 22 It was found that a Co atom captured by a CoPc molecular mold locates either above or beneath an isoindole unit of the Pc ring. In the former case, the Co atom is exposed to the open air, and may thus act as an SAC for CO oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The DFT+HEOM approach has been successfully applied to describe the Kondo spin-screening effect in magnetic atom adsorbed on the metal support. 22,42,43 Density functional theory calculation. The Perdew-Burke-Ernzerholf (PBE) generalized gradient approximation implemented in the Vienna ab initio simulation package 44 is employed, with the DFT-D3 method of Grimme 45 used to improve the description of van der Waals interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation